Civil Society Organizations (CSO) di aras lokal :: Studi tentang partisipasi konsorsium Makuwaje dalam perumusan kebijakan publik di Provinsi Maluku Utara - Isman, ABAS ([Yogyakarta] : Universitas Gadjah Mada, 2006)
In a democratic governmental system, the concept of society participation is one of the important concepts because it is directly related to the essence of democracy as a governmental system focused on people as sovereignty owner. In the context of public policy formulation, participation is a key word that has to be realized and practiced by Local Government, so public policy no longer becomes Local Government’s affairs only. The changes of political constellation following decentralization of politic in New Order brought very great implications on local polity. In this regard Local Government does not have other choices but enforcing reformation for good governance. The momentum of political openness at post-New Order is really meant as an important one for the emergence of Non-governmental organizations (NGOs) with their various roles. The presence of NGOs in society is an undeniable fact. It is due to the limitedness of government’s role and capacity in almost all sectors of development, so not all aspirations and need of society can be met by government. NGOs, however, tend to be involved in political process not especially to struggle for governmental power but also to take part as interest groups as well as pressure groups, mainly in each public policy formulation by government bureaucracy and legislative. This research is conducted to find out the characteristics of Civil Society Organization (CSO) in North Maluku, especially as far which the participation of Makuwaje Consortium in public policy formulation and which factors bring effect to it. The research is qualitative one and uses a descriptive-analytical method with approach to case study in explaining facts collected. Data exploration is conducted by using the technique of in-depth interview with some informants that represent Local Government, Legislative Assembly at Local Level, Makuwaje Consortium, and others understanding the problems researched. The result of the research indicates that the characteristics of Civil Society Organizations (CSO) at the local level in North Maluku are that the NGOs are still very pragmatic in orientation and often involved in ethnic contestation. In general, NGOs’ activity in North Maluku is not related to the needs of post-conflict society but tend to follow trends (not demand- or local-driven, but trend-driven activity). The involving of NGOs in public policy formulation by Local Government tends to meet needs for political legitimacy only. In general, the stages of Local Budget (APBD) formulation in North Maluku can not be used as information channels by Makuwaje Consortium due to the reticence of Local Government and Legislative Assembly at Local Level. It is deliberately conditioned to continuously perpetuate the domination of Local Government and Legislative Assembly at Local Level in Local Budget (APBD) formulation process. It is due to the fact that in performing its activities, Makuwaje Consortium still faces obstacles and weakness internally: the lack of experiences in carrying out advocating efforts, weakness in developing networks, and tends to be influenced by the responses of both Local Government and donor institutions. The condition really made the participation of Makuwaje Consortium not maximal in public policy formulation process in North Maluku.